Clinical features and prognosis of paediatric rhabdomyosarcoma with bone marrow metastasis: a single Centre experiences in China - Cheng Huang; Binglin Jian; Yan Su; Na Xu; Tong Yu; Lejian He; Xue Zhang; Yi Liu; Mei Jin; Xiaoli Ma (BMC, 2021)
Abstract Background The aim of this study was to summarize the clinical characteristics, therapeutic effects and prognosis of patients with rhabdomyosarcoma (RMS) and bone marrow metastasis, improve the understanding of this disease. Method This was a single-institution retrospective study involving the children with RMS, who presented with bone marrow metastasis at initial presentation to our hospital between 1st, Jan, 2006 and 31st, Dec,2019. Follow-up concluded on 31st, Dec, 2020 and the clinical data were collected and analysed. Result Between 1st Jan 2006 and 31st Dec 2019, 13 eligible patients presented to our hospital, including 10 males and 3 females, these eligible patients accounted for 4.5% of all RMS patients. The median age at onset was 5.6 years (range 1.7-14 years). The patients not only had unfavourable primary sites, but also had multiple metastases. The bone marrow aspirate samples of the patients comprised 8-95% blast-like cells. Nine of 13 patients were misdiagnosed with haematological malignancies or other solid tumours. With respect to histology, four of 13 children were classified as embryonal RMS and nine as alveolar RMS. Eleven patients underwent PAX-FOXO1 fusion testing; eight had the POX- FOXO1 fusion gene. Immunohistochemically(IHC) analysis revealed that the tumour cells were positive for Desmin, Vimentin, Myo-D1 and Myogenin. More importantly, the patients had extremely poor prognoses, the median EFS was 12.0 months (range 3-28.3 months) and the median OS was 27.0 months (range6-46.2 months). Conclusion This study demonstrates that children with RMS and bone marrow metastasis usually exhibit atypical primary sites and multiple metastases, with presentation mimicking haematological malignancies or other solid tumors at initial presentation. Pathology and IHC analysis combined with POX-FOXO1 fusion gene detections can effectively confirm the diagnosis. These patients are more likely to relapse or progress during early treatment and are prone to intracranial metastasis. While multidisciplinary therapy combined with Temozolomide may prevent it, further prospective research is required to evaluate the therapeutic effects.